Muscle fatigability in patients with type 2 diabetes: relation with long‐term complications. Issue 2 (11th November 2019) - Orlando, Giorgio; Sacchetti, Massimo; D'Errico, Valeria; Haxhi, Jonida; Rapisarda, Gianvito; Pugliese, Giuseppe; Balducci, Stefano
Abstract: Aims: It is unclear whether long‐term complications play a role in muscle fatigue characteristic of patients with type 2 diabetes mellitus (T2DM). The purpose of this study was to investigate the association between muscle fatigability and microvascular and macrovascular complications in patients with T2DM. Methods: One‐hundred forty‐six patients with T2DM (80 males, 66 females, aged 66.9 ± 7.9 years) were recruited. Maximal voluntary contraction (MCV) and endurance time (ET, 50% of the MVC) were assessed at the knee extensor muscles with an isometric dynamometer. Univariate and multivariate correlations of ET values with diabetic complications, a wide range of surrogate measures of these sequelae, and cardiovascular risk factors were examined. Results: A higher muscle fatigability was detected in patients with diabetic peripheral neuropathy (DPN, ET: −32.4%), cardiovascular disease (CVD, ET: −32.1%), retinopathy (ET: −35.8%), and nephropathy (ET: −30.4%). At univariate analysis, muscle fatigability was associated with age, physical activity level, diabetes duration, HbA1c, systolic blood pressure, albuminuria, eGFR, and several parameters of nervous and vascular function. Multivariate analysis showed that, after adjusting for covariates, ET was independently associated with sensory nerve conduction velocity, vibration perception threshold at malleolus, and ankle‐brachial index. In addition, ET values were independently associated with the presence of DPN, CVD, and retinopathy. Conclusions: In T2DM, muscle fatigability is associated with presence of DPN, CVD, and retinopathy. Such defect appears to be mediated predominantly by sensory nerve and peripheral vascular dysfunction.